1971
DOI: 10.1152/ajplegacy.1971.221.4.1192
|View full text |Cite
|
Sign up to set email alerts
|

Potassium transport across renal distal tubules during acid-base disturbances

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
45
2
1

Year Published

1973
1973
1996
1996

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(57 citation statements)
references
References 40 publications
9
45
2
1
Order By: Relevance
“…The finding of progressive reabsorption of potassium along the distal convoluted tubule in normal rats is in agreement with the observations of Marsh, Ullrich, and Rumrich (6), but conflicts with several studies by Malnic, Klose, Giebisch, and de Mello Aires (7)(8)(9). These latter authors have reported that under a variety of different experimental conditions, tubular fluid potassium concentration rises at the end of the distal tubule to levels severalfold higher than plasma concentration, and that there is net addition of potassium to the tubular fluid by the distal convoluted tubule.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The finding of progressive reabsorption of potassium along the distal convoluted tubule in normal rats is in agreement with the observations of Marsh, Ullrich, and Rumrich (6), but conflicts with several studies by Malnic, Klose, Giebisch, and de Mello Aires (7)(8)(9). These latter authors have reported that under a variety of different experimental conditions, tubular fluid potassium concentration rises at the end of the distal tubule to levels severalfold higher than plasma concentration, and that there is net addition of potassium to the tubular fluid by the distal convoluted tubule.…”
Section: Discussionsupporting
confidence: 89%
“…These latter authors have reported that under a variety of different experimental conditions, tubular fluid potassium concentration rises at the end of the distal tubule to levels severalfold higher than plasma concentration, and that there is net addition of potassium to the tubular fluid by the distal convoluted tubule. Only under conditions of a low potassium diet (7), or severe metabolic or respiratory acidosis (9) did net reabsorption of potassium occur in the distal tubule. The reason for the difference between our observations and those of Malnic and co-workers is not clear, but several possibilities can be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, potassium handling has been suggested to be another regulator: potassium loading in dogs increases K secretory fluxes and suppresses the rate of distal nephron hydrogen ion secretion (4). However, in rat distal tubule micropuncture studies, no evidence of a reciprocal relationship between distal tubular K and hydrogen ion secretory rates could be obtained (8).…”
Section: Introductionmentioning
confidence: 95%
“…The isolated cortical collecting duct of the rabbit has been shown capable of adding potassium to the urine (21), as has the papillary collecting duct of the hamster (22). Several studies by Malnic and Giebisch and their associates in rats, however, failed to demonstrate net addition of potassium to the urine beyond the distal convoluted tubule (7,23), and Diezi et al were unable to show net potassium secretion consistently in the papillary collecting duct of the rat (24). More recently, Bank and Aynedjian have been able to demonstrate the addition of potassium to the final urine at a point distal to the micropunctured cortical distal convolution in partially nephrectomized rats subjected to potassium loads.…”
Section: Resultsmentioning
confidence: 99%